Solve the following pair of linear equations by the substitution method.

s – t = 3

`s/3 + t/2 = 6`

Advertisement Remove all ads

#### Solution

s – t = 3 (1)

`s/3 + t/2 = 6`

From (1), we obtain

s = t + 3 (3)

Substituting this value in equation (2), we obtain

`(t + 3)/3 + t/2 = 6`

2t + 6 + 3t = 36

5t = 30

t = 6 (4)

Substituting in equation (3), we obtain

s = 9

∴ s = 9, t = 6

Concept: Algebraic Methods of Solving a Pair of Linear Equations - Substitution Method

Is there an error in this question or solution?

#### APPEARS IN

Advertisement Remove all ads